2022
DOI: 10.1108/bij-09-2021-0541
|View full text |Cite
|
Sign up to set email alerts
|

How do the technological capability and strategic flexibility of an organization impact its successful implementation of Industry 4.0? A qualitative viewpoint

Abstract: PurposeIndustry 4.0 (I 4.0) consists of numerous digital technologies applied in organizations strategically to add value to the customer. Different organizations have varying degrees of technological capability and strategic flexibility. This paper aims to explore the relationship between technological capability and strategic flexibility on successful implementation of I 4.0.Design/methodology/approachA qualitative study using a grounded theory approach is conducted on 34 senior managers from Europe and Nort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 117 publications
0
6
0
Order By: Relevance
“…These are as follows: According to Adebanjo et al . (2023) and Sony et al . (2023), the preparation for the adoption of Industry 4.0 practices within the organization requires the greatest attention to be paid to the training and education of the workforce.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…These are as follows: According to Adebanjo et al . (2023) and Sony et al . (2023), the preparation for the adoption of Industry 4.0 practices within the organization requires the greatest attention to be paid to the training and education of the workforce.…”
Section: Resultsmentioning
confidence: 97%
“…The significance of these Industry 4.0 enablers for the organizations implementing Industry 4.0 has been highlighted in the previous studies. These are as follows: According to Adebanjo et al (2023) and Sony et al (2023), the preparation for the adoption of Industry 4.0 practices within the organization requires the greatest attention to be paid to the training and education of the workforce. According to Antony et al (2023), company culture has a major influence on innovation as well as creativity.…”
Section: Resultsmentioning
confidence: 99%
“…Employees technological capability will assist them in boosting efficiency, speed, accuracy, productivity, and performance, which will affect the ability of the firm to be competitive constantly. Employees who have low technological capabilities can cause technostress and decrease performance and productivity (Al-Mamary et al, 2022;Baskaran et al, 2020;Salisu & Bakar, 2020;Sony et al, 2022;Santoso et al, 2021).…”
Section: Technology Capabilitymentioning
confidence: 99%
“…Previous research also revealed that technological capabilities could be seen from the ability to identify technology, design technology, apply technology, and utilise technology (Joshi et al, 2021). In addition, technological capability could be seen from the ability to obtain, operate, accept, and improve technology (Sony et al, 2022).…”
Section: Technology Capabilitymentioning
confidence: 99%
“…The biggest opportunity is the increase of customers' trust in internet transactions, and the biggest threat is the resistance of employees toward the adoption of new technologies. A study by Sony et al (2022) reveals that technological capabilities and strategic flexibility influence the successful implementation of Industry 4.0, which consists of a range of digital technologies. Ghouchani et al analyze the impact of using the internet of things on the development of electronic business.…”
Section: Research Backgroundmentioning
confidence: 99%